Assessment of canal walls after biomechanical preparation of root canals instrumented with protaper universalTM rotary system - Carlos Menezes Aguiar; Daniela de Andrade Mendes; Andréa Cruz Câmara; Antonio Poli de Figueiredo (University of São Paulo, 2009)
OBJECTIVE: The aim of this study was to examine the instrumented walls of root canals prepared with the ProTaper UniversalTM rotary system. MATERIAL AND METHODS: Twenty mesiobuccal canals of human first mandibular molars were divided into 2 groups of 10 specimens each and embedded in a muffle system. The root canals were transversely sectioned 3 mm short of the apex before preparation and remounted in their molds. All root canals were prepared with ProTaper UniversalTM rotary system or with NitiflexTM files. The pre and postoperative images of the apical thirds viewed with a stereoscopic magnifier (X45) were captured digitally for further analysis. Data were analyzed statistically by Fisher's exact test and Chi-square test at 5% significance level. RESULTS: The differences observed between the instrumented and the noninstrumented walls were not statistically significant (p<0.05). CONCLUSIONS: The NitiflexTM files and the ProTaper UniversalTM rotary system failed to instrument all the root canal walls.